2021
DOI: 10.1177/1558925021992757
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the color stripping of the pigment printed cotton fabric using the ozone assisted process: A study on the decolorization and characterization

Abstract: Color stripping is one of the most convenient ways to rectify the various shade faults occurred during printing or dyeing process of textiles. But, the conventional chemical assisted process poses serious risk of the environmental pollution. Secondly, the chemical recycling of the cellulosic fibers may be disrupted due to the presence of the impurities like colorants, finishes, and the additives in the discarded textiles. So, there is a need to study ways to remove such impurities from the discarded cellulosic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The CIELAB color space commonly known as CIE L*a*b* was defined in 1976 by the International Commission on Illumination (CIE). In the CIELAB color space, L* stands for the lightness (0 = black, 100 = white), a* stands for the red-green coordinate from (positive sign = red, negative sign = green) and b* stands for the yellow-blue coordinate from (positive sign = yellow, negative sign = blue) [7].…”
Section: Cielab Methodology For the Color Analysismentioning
confidence: 99%
“…The CIELAB color space commonly known as CIE L*a*b* was defined in 1976 by the International Commission on Illumination (CIE). In the CIELAB color space, L* stands for the lightness (0 = black, 100 = white), a* stands for the red-green coordinate from (positive sign = red, negative sign = green) and b* stands for the yellow-blue coordinate from (positive sign = yellow, negative sign = blue) [7].…”
Section: Cielab Methodology For the Color Analysismentioning
confidence: 99%
“…Various research on dye removal has been done with recent work that carries out the decolorization process of textile fabrics at a pilot scale using an ozone-assisted process. 111 Powar et al 111 decolorized 90% and above pigment-printed cellulosic textiles using the ozoneassisted process in an acidic solution. He et al 112 concluded that ultraviolet (UV)/Na 2 S 2 O 4 with a photocatalytic system could effectively strip fixed reactive dyes, with a relatively high tensile strength retention observed from cotton fibers.…”
Section: Mixed Knitted Fabrics [91]mentioning
confidence: 99%
“…Various research on dye removal has been done with recent work that carries out the decolorization process of textile fabrics at a pilot scale using an ozone-assisted process. 111 Powar et al. 111 decolorized 90% and above pigment-printed cellulosic textiles using the ozone-assisted process in an acidic solution.…”
Section: Textile Recycling Technologiesmentioning
confidence: 99%
See 1 more Smart Citation